2022
DOI: 10.3389/fcvm.2022.938363
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidemia and the Prevalence of Hypertension: A Cross-Sectional Study Based on Chinese Adults Without Type 2 Diabetes Mellitus

Abstract: BackgroundIn clinical practice, it is frequently observed that patients with hypertension often coexist with dyslipidemia. However, studies on atherosclerotic indices and the prevalence of hypertension are still limited. The purpose of this study was to assess the relationship between atherosclerotic indices and the prevalence of hypertension in Chinese adults without type 2 diabetes mellitus.MethodsIn this paper, a cross-sectional study was conducted based on 117,056 adults in 11 Chinese cities (Shanghai, Bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 52 publications
0
3
0
2
Order By: Relevance
“…Проведенное исследование показало, что липитензия у мужчин встречается чаще, чем у женщин, а шанс наличия липитензии у молодых лиц мужского пола возрастал в 2,6 раз. Эти данные согласуются с результатами исследования, проведенного в России [6], но отличаются от зарубежных данных, где липитензия встречалась чаще у женщин [7], что может объясняться этническими и межкультурными особенностями [8]. Важно отметить, что липитензия была установлена у каждого 4 пациента, тогда как изолированное повышение АД без ДЛП только в 13,1% случаев.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Проведенное исследование показало, что липитензия у мужчин встречается чаще, чем у женщин, а шанс наличия липитензии у молодых лиц мужского пола возрастал в 2,6 раз. Эти данные согласуются с результатами исследования, проведенного в России [6], но отличаются от зарубежных данных, где липитензия встречалась чаще у женщин [7], что может объясняться этническими и межкультурными особенностями [8]. Важно отметить, что липитензия была установлена у каждого 4 пациента, тогда как изолированное повышение АД без ДЛП только в 13,1% случаев.…”
Section: Discussionunclassified
“…Лица с липитензией чаще имели АО (31,2%), повышение гликированного гемоглобина (HbA 1c ) >6% (39%) и инсулинорезистентность (36,2%), чем без липитензии (р=0,026, р=0,018, р=0,044, соответственно). При липитензии установлены: более высокий уровень висцерального жира (Ме 8 [6][7][8][9]…”
Section: липитензия и факторы кардиометаболического риска в молодом в...unclassified
See 1 more Smart Citation
“…Secondly, several studies have demonstrated significant associations between elevated AIP level and insulin resistance, which is associated with an augmented susceptibility to cardiovascular events [ 30 ]. Thirdly, patients with a high AIP level were more likely to be obese [ 31 ], and manifest a greater incidence of hypertension, diabetes mellitus, and metabolic syndrome [ 32 34 ], all of which which are essential players in poorer clinical outcomes following PCI.…”
Section: Discussionmentioning
confidence: 99%
“…Another longitudinal study also showed that in Taiwan, China, the association of AIP with hypertension was stronger in men than in women [ 16 ]. However, a large cross-sectional study observed no significant relevance between AIP and hypertension among adults without type 2 diabetes mellitus (T2DM) in China [ 19 ]. So, the evidence regarding the association between AIP and hypertension is still contradictory and uncertain, especially in different sex, age and ethnicity of population.…”
Section: Introductionmentioning
confidence: 99%